Modified Halophyte Biochar for Congo red Removal: Adsorption and Neural Prediction - Mehta, Disha P.; Dave, Pragnesh N.; Sirach, Ruksana R.; Kumar, Vijay V. (Sustainability & Circularity NOW, 2025)
Adsorption is widely recognized as a reliable and cost-effective technique for the removal of dye pollutants from aqueous environments. This study investigates a novel adsorbent—ferrite composite of biochar (FCOB) for Congo red (CR) dye removal. It was synthesized by pyrolyzing Suaeda monoica leaf powder to obtain biochar, followed by base treatment to produce base-treated biochar, and subsequent coprecipitation with NiCuZnFe₂O₄ ferrite spinel. The XRD analysis of FCOB confirmed the successful incorporation of spinel NiCuZnFe2O4 into FCOB, as evidenced by the presence of two prominent characteristic peaks of the spinel structure. The SEM image revealed the irregular-crumpled structure of FCOB. BET analysis revealed the mesoporosity in FCOB, with a surface area of 44.64 ± 0.2396 m2 g−1. The optimum adsorption was achieved at a pH of 2, adsorbent dosage of 20 mg, initial CR concentration of 50 mg/L, contact time of 320 min, and temperature of 85 °C. The maximum CR dye removal percentage (R%) was 99.75%. At pH = 2, the strong electrostatic attraction between protonated FCOB adsorbent and anionic CR seemed to be the dominant adsorption mechanism. The adsorption data was best (R2 = 0.99) described by the Redlich–Peterson isotherm model, indicating a heterogeneous surface with some degree of monolayer adsorption. The maximum adsorption capacity estimated from the Langmuir model was qmax = 239.80 mg/g. The adsorption kinetics data was best described by pseudo-second-order model (R2 = 0.99), suggesting that chemisorption is likely the rate-limiting step. The CR adsorption process was spontaneous and endothermic with ΔH° = 71.02 ± 1.41 kJ/mol. ANN analysis revealed that both BR and LM algorithms accurately predicted removal efficiency and adsorption capacity, achieving R values greater than 0.995. FCOB could also be regenerated and recycled up to 5 cycles retaining ≅65% removal efficiency for CR. Therefore, FCOB can serve as a biodegradable, cost-effective, nontoxic, and renewable adsorbent in treating CR-dye contaminated industrial wastewater, especially from textile and printing sectors.
Keywords: Congo red; Adsorption; Biochar; Suaeda monoica; Ferrite spinel